2014
DOI: 10.1210/en.2014-1565
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Histone Deacetylase 1 (HDAC1) But Not HDAC2 Is Required for the Glucocorticoid-Dependent CCAAT/Enhancer-Binding Protein α (C/EBPα) Expression and Preadipocyte Differentiation

Abstract: Several drugs currently used in the management of mood disorders, epilepsy (ie, valproic acid), or the control of inflammation (ie, corticosteroids) have been shown to promote visceral obesity in humans by increasing the number of newly formed adipocytes. Valproic acid is classified as a nonspecific histone deacetylase (HDAC) inhibitor, along with trichostatin A and butyric acid. In vitro experiments have demonstrated that such molecules greatly enhance the rate of preadipocyte differentiation, similarly to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“…In BAT, this is associated with an enrichment of GO terms associated with DNA metabolism (i.e. histone deacetylation) with CTBP1, HDAC1 and SIRT2 all previously shown to be negative regulators of lipogenesis by either binding or deacetylating PPARY [24-26]. In IWAT, we show an enrichment of proteins involved in retinol metabolism, a well-known pathway which drives both adipogenesis and lipogenesis which is dependent on an intact NAD+ binding motif [27].…”
Section: Discussionmentioning
confidence: 79%
“…In BAT, this is associated with an enrichment of GO terms associated with DNA metabolism (i.e. histone deacetylation) with CTBP1, HDAC1 and SIRT2 all previously shown to be negative regulators of lipogenesis by either binding or deacetylating PPARY [24-26]. In IWAT, we show an enrichment of proteins involved in retinol metabolism, a well-known pathway which drives both adipogenesis and lipogenesis which is dependent on an intact NAD+ binding motif [27].…”
Section: Discussionmentioning
confidence: 79%
“…Valproic acid, classified as a nonspecific HDAC inhibitor, along with trichostatin A and butyric acid, are commonly used in the management of mood disorders and epilepsy to promote visceral obesity in humans by increasing newly formed adipocytes, similar to corticosteroids. It has been shown that glucocorticoid receptor stimulates adipogenesis in part by enhancing the transcription of C/ebpa through the titration, and subsequent degradation, of HDAC1 from the C/ebpα promoter (Kuzmochka et al, 2014). Therefore, targeting HDAC1 (likely through activation) may serve as a possible avenue to prevent glucocorticoid-induced adiposity through regulation of CCAAT/enhancer-binding protein α (C/EBPα) levels in preadipocytes.…”
Section: Role Of Histone Modification In Obesogenesis and Cardiomyopathymentioning
confidence: 99%
“…HDACs do not only modulate the acetylation of histones but also of non-histone proteins such as DNA binding transcription factors, steroid receptors, transcription coregulators and chaperone proteins (Glozak & Seto 2007). Recent data by Kuzmochka et al (2014) show that inactivation of HDAC1 promotes adipose conversion. However, other studies indicate that inhibitors of HDACs repress expression of the late markers of differentiation CEBPa (Catalioto et al 2009) and aP2 (Haberland et al 2010) and curb adipogenesis.…”
Section: Modulation Of Mr Activity By Adipogenic Signaling Pathways Amentioning
confidence: 99%